Analysis of microearthquakes with correlation method at salavatli geothermal area, Aydın - Kalkan, Esra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Induced seismicity typically refers to minor earthquakes and tremors that are caused by human activity that alters the stresses and strains on the Earth's crust. Earthquakes which are smaller magnitude are called micro-earthquakes. Micro-earthquakes could be observed in areas which includes energy technologies that involve injection or withdrawal of fluids from the subsurface. Micro-earthquakes are the result from these kind of process. Geothermal areas are good example of that kind of areas. So we chose Salavatlı, Aydın geothermal area to study. The main aim of this study is to find similar micro-earthquakes with correlation method to check if they come from same source or location. So the data which was collected from 9 broad-band stations which were installed at the study area,between June of 2010 and April of 2013 were used for this aim. 977 micro-earthquakes were located with SEISAN. 815 of them could be used for the correlation analysis due to quality of data. GISMO correlation toolbox was used for this process. The duration of waveforms are 10 seconds because the longest micro-earthquake in this study is 8 seconds. We took lower limit as 0.9 for the correlation co-efficient. 34 event of similar waveforms were found. When we examined location of all micro-earthquakes, we saw that they were scattered over the study area. This might be caused from wrong P or S wave pickings or inadequate crustal velocity model. So, firstly, we decided to check the initial velocity model by using VELEST software. For the VELEST processing 334 best located micro-earthquakes were selected on the base some criterias. After getting minimum 1D velocity model for the study area, all micro-earthquakes were relocated again and then mapped. The location of most of them altered and get better. Then with final 1D velocity model, events of similar waveforms were map. In general, when monthly location of micro-earthquakes were checked, the direction of the injected water from re-injection wells could be clearly seen on the seismicity maps.
Keywords: Microseisms -- Turkey -- Aydın.; Earthquakes -- Turkey -- Aydın.; Geothermal Resources.